The Effect of Hand Blood Flow on the Peripheral Fingertip Plethysmographic Waveforms Morphology and Pulse Wave Velocity - Sheamaa Ahmed Abdullah, Samar I. Essa, Bassam Talib, (Pakistan Journal of Medical & Health Sciences, 2022)
Photoplethysmography (PPG) is a non-invasive optical technique that employs variations in light absorption produced by alteration in the blood volume in capillaries at the skin during the cardiac cycle. This study aims to understand factors related to PPG morphology; a hand-elevation, the study has modified blood flow to and from the finger was conducted in the laboratory. It is widely established that the position of the limb relative to the heart has an effect on blood flow in arteries and venous. Peripheral digital pulse wave (DPW) signals were obtained from 15 healthy volunteer participants during hand-elevation, and hand-lowering techniques wherein the right hand was lifted and lowered relative to heart level, while the left hand remained static. The pulse width, time to peak (TTP), the time to the maximum slope (TTMas) were computed from 30sec DPW signals at three positions of the right hand with regard to heart level, i.e. 35 cm above heart level (+35 cm), at the level of the heart (0 cm), and 35 cm below the level of the heart (-35 cm). DPW characteristics were found to alter with hand position. On lowering the hand to -35 cm relative to heart level, DPW width from the middle finger increased by (6%), but lowering the arm decreased the TTP (by 11 %), TTMas (by 18 %). These changes in time-dependent DPW indices may be attributed to changes in hydrostatic pressure and the venoarterial reflex that changes the blood vessels filling from completely filled one at -35 cm due to arterial vasoconstriction and decreased venous return to partially emptied blood vessels due to arterial vasodilatation and increased venous return at +35 cm. It was assumed that these time-dependent morphological DPW indices alterations were controlled by changes in downstream venous resistance rather than arterial or arteriolar, resistance. Keywords: photo plethysmography, hand elevation, vasoconstriction, vasodilation, vascular mechanics